CREATION OF UNISCOPE: A MODEL FOR REWARDING ALL FORMS OF SCHOLARSHIP - Gurgevich, Elise A.; Hyman, Drew; Alter, Theodore R. (Online Learning, 2003)
On March 24, 1998, a small group of faculty and administrators at the Pennsylvania State University (PSU) formed a learning community to engage in a deliberative dialogue about recognizing and documenting outreach scholarship in the University. We chose UniSCOPE, University Scholarship and Criteria for Outreach and Performance Evaluation, as a title to encapsulate our mission. Our goal was to consider the meaning of scholarship in the contemporary university and to consider the role of outreach therein. We did this in the context of the Penn State promotion and tenure system to gain a better understanding of its effect on scholarship. We quickly learned that outreach scholarship cannot be examined in isolation, and we broadened our deliberations to consider the full range of scholarship. This report articulates a multidimensional model of scholarship in general, of which outreach scholarship is a key component and presents our recommendations for action.